Biokapazitive Resilienz – Leitbild und Strategie zum Aufbau einer schützenden Raumökologie. Steuerungschancen für die Raumordnungspraxis im Kontext einer klimaresilienten Entwicklung? - Hüppauff, Jakob (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
Merely safeguarding ecologically spatial functions is not (or no longer) sufficient to maintain their ability to function in the course of climate change and under increasing pressure of use. Rather, a fundamental change of perspective also in spatial planning practice is required to build up a resilience-proof spatial ecology, especially due to the tension between biomass production, carbon storage and biodiversity protection. In this context, biocapacity resilience is put forward for discussion as an impetus for a guiding vision of spatial development. Possible opportunities for the actors of spatial planning are elaborated to better fulfil their regional steering mandate in the sense of precautionary planning under the lens of global challenges despite limited resources.